2023
DOI: 10.7759/cureus.35651
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Coronary Stent Technologies - A Glimpse Into the Future

Abstract: One of the most widely accepted forms of treatment for coronary artery disease (CAD) is the implementation of stents into the vessel. This area of research is constantly evolving, ranging from baremetal stents through drug-eluting stents and, more recently, approaching bioresorbable stents and polymerfree stents. This article reviews the evolution of all these devices and emphasizes how they might be further evolved to provide an optimal coronary stent and overcome unsolved challenges in stent development. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…GES utilize stents as carriers for the localized delivery of therapeutic genes, potentially overcoming the limitations of traditional gene therapy. Studies have demonstrated the precise transport of plasmid genes such as GFP and VEGF through bioabsorbable stents, offering new therapeutic avenues for the treatment of vascular lesions ( 49 ).…”
Section: Novel Materialsmentioning
confidence: 99%
“…GES utilize stents as carriers for the localized delivery of therapeutic genes, potentially overcoming the limitations of traditional gene therapy. Studies have demonstrated the precise transport of plasmid genes such as GFP and VEGF through bioabsorbable stents, offering new therapeutic avenues for the treatment of vascular lesions ( 49 ).…”
Section: Novel Materialsmentioning
confidence: 99%
“…Approximately 5 million percutaneous coronary interventions (PCI) are performed annually worldwide [ 1 , 2 , 3 ]. Atherosclerosis is one of the most recurring inflammatory problems produced in the coronary arteries in the last years around the world [ 4 , 5 , 6 , 7 ]. Stenting is an important treatment to allow blood to flow through narrowed coronary arteries [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%